Quantifying the value of transitions in soccer via spatiotemporal trajectory clustering - Hobbs, J.; Power, P.; Sha, L.; Ruiz, H.; Lucey, P. (2018)
In recent years, the "counter-press", "geggenpress" and "counter-attack", have been in vogue due to their ability to create good scoring chances by effectively overloading the team that has just lost the ball. These "transitions" capture how effective a team is as they transit from defense to offense (and vice-versa) without any stoppage in play. Counter-attacks, a sub-category of transitions which are especially fast-paced, aggressive, and direct, provide some of the best opportunities for scoring and are a potent strategy when executed effectively [1]. Specifically, if a team counters immediately (creating a chance less than 15sec after regaining the ball), the likelihood of scoring is 12.4% vs 8.0% (p-value<0.01), when they look to maintain possession. Additionally, the likelihood of a team obtaining a shot is 35.1% vs 10.6% (p-value<0.01).